Proceso de recaudación de los ingresos del GAD Municipal Babahoyo - Zambrano Moyano, Carlos Eduardo (2018)
In Ecuador, as in all countries of the world, there are legal regulations where all the people of the nation in contributory capacity to pay taxes, but to what we call tribute? we call tribute to the monetary value that the citizen is obliged to pay or citizen for the sole purpose of these values ​​being remunerated in public works by of the state that benefit the whole community and that lead citizens to have a better Lifestyle. This country has undoubtedly had a total revolution in what concerns the collection of tax from the government of Eco. Rafael Correa Delgado and thanks to the work done of the SRI (Internal Revenue Service), but the outstanding debt persists in the governments sectionals, where there is a big problem when collecting the taxes that are of your competition The Municipal Autonomous Decentralized Government of the Babahoyo Canton has to its credit the tax administration of all the territory of the city where the collected values by the treasury department allow you to carry out your self-management, each public contribution is intended for a specific item where the lack of payment of the citizens of Fluminense prevent the Municipality from carrying out its functions and in turn reduce the works for the benefit of Babahoyans citizens. The municipality of Babahoyo like all the municipalities of the country present the same problem, the non-payment of taxes, in total GAD Babahoyo has to his credit 48 taxes and each of them presents difficulties for its normal collection. The process of tax collection is the selected topic to carry out the present study of case to the AUTONOMOUS DECENTRALIZED GOVERNMENT OF CANTON BABAHOYO, the same one that will be studied due to the low collection rate of the sectional taxes by for of this entity, where we will evaluate the reason of the lack of 2 payment of taxpayers, which are the taxes that cause most problems to the municipality to collect and how this problem affects the company. The use of interview, dialogue and personal analysis are the techniques chosen for the information gathering as a deductive research method for the specific purpose to locate the synthesis of the problem and know what are the measures taken by the entity to counter this problem